Recent advances in mesoporous silica nanoparticle: synthesis, drug loading, release mechanisms, and diverse applications - Fatima, Rabia; Katiyar, Pratima; Kushwaha, Kalpana (Frontiers in Nanotechnology, 2025)
Despite significant advancements in pharmaceutical sciences, conventional drug delivery system remains limited by issues like poor permeability, toxicity, suboptimal efficacy, and inadequate targeting. These challenges pose substantial barrier to effective treatment for complex conditions like cancer, heart problems, chronic pain management, etc. Mesoporous silica nanoparticle (MSN), with their remarkable structural tunability and multifunctionality, have emerged as a transformative solution in the realm of drug delivery system. This review delves into the state-of-the-art synthesis methods of MSNs including physical, chemical, top down and bottom-up approaches with particular attention to the widely used Sol-Gel process. We also explore innovative drug loading strategies and controlled release mechanisms, underscoring how factors such as pore size, particle shape, and surface charge influence therapeutic outcomes. Furthermore, we highlight the burgeoning applications of MSNs across multiple domains, ranging from anticancer therapy and gene delivery to emerging fields such as precision agriculture and environmental remediation. Recent studies demonstrate the versatility of MSNs in addressing both biomedical and ecological challenges, making them an indispensable tool in modern science. By synthesizing Collectively, this review aims to provide a comprehensive resource for researchers and practitioners, fostering continued innovation in the design and application of MSN-based nanotechnology.